Artificial Intelligence Readiness in Malaysian Libraries: An Assessment Framework - Masrek, Mohamad Noorman; Mohamad Rosman, Mohamad Rahimi; Baharuddin, Mohammad Fazli; Mohamed Shuhidan, Shamila; Mutia, Fitri; Yuwinanto, Helmy Prasetyo; Atmi, Ragil Tri; Soesantari, Tri (PT Mattawang Mediatama Solution, 2025)
This study investigates the readiness of Malaysian libraries to embrace Artificial Intelligence (AI) technologies, focusing on six key dimensions: infrastructure, technical skills, management support, policy and regulations, funding, and training. Utilizing a quantitative research approach, an online survey was conducted to collect data from library heads, providing insights into their preparedness for AI adoption. The survey instrument, developed based on preliminary interviews with librarians and refined through expert feedback and pilot testing, achieved good internal consistency. Findings reveal that while libraries exhibit moderate readiness in terms of internet infrastructure and management support, significant challenges remain in financial planning and policy and regulation formulation for AI integration. These challenges highlight critical areas that need addressing for successful AI adoption. The study provides valuable insights for library administrators and policymakers, emphasizing the need for comprehensive strategies to enhance AI readiness. The contributions of this study are threefold. Theoretically, it expands the understanding of AI readiness in the library sector, offering a validated framework for future research. Empirically, it fills a gap by providing data-driven insights into the current state of AI readiness among Malaysian libraries. Practically, it offers actionable recommendations to improve financial planning and policy development, essential for effective AI integration.